The Influence Of The Quality Of Mobile Banking Services On Customer Loyalty At The Bni Bank, Bumi Tamalanrea Permai - Savira, Reza; Aslinda, Andi; Siraj, Muhammad Luthfi; Kasmita, Maya (Universitas Negeri Makassar, 2024)
This study aims to determine the effect of the quality of mobile banking services on customer loyalty at BNI Bank Bumi Tamalanrea Permai Cash Office. The research method used was quantitative method with data collection techniques namely observation, questionnaires and documentation, and analyzed using descriptive statistical analysis techniques and inferential statistical analysis techniques with a study population of 945 customers and a sample of 90 customers in this study. The data obtained from the research results were processed using data analysis and using the SPSS software application which consisted of validity and reliability tests, percentage descriptive analysis techniques, simple linear analysis and T tests. The results of the research and data analysis in this study regarding the effect of mobile banking service quality on customer loyalty at BNI bank, Bumi Tamalanrea Permai office in the very good category, based on these data, there is a significant influence between service quality and customer loyalty, customers are satisfied with the service provided. given, where from the results of the product moment correlation test analysis, namely r count is greater than r table which means that service quality partially has an influence on customer loyalty. Keywords: Service Quality, Customer Loyalty